Apologetic Evangelical Contextual Christology: A Pragmatic Approach in the Islamic Context (Pakistan) - Aftab Yunis Hakim (Religions, 2024)
The conflict over Jesus Christ, the ‘Son of God’, is not new. Thousands of years ago, the disciples faced similar trials; however, the challenge to solve this tension was not based on debates or natural theology but rather to show the works of Christ. This researcher argues that various studies on Christology have already been conducted. However, the Pakistani perspective demands the fullness of Christ in a unique way to reimagine Him in the context of socio-economic, political, and religious challenges. On the one hand, though the traditional way of doing Christology highly emphasizes the personhood of Christ, explaining Him from the eschatological perspective (though it is important), on the other hand, it makes Christ an aloof Jesus who has no concern for the current issues. As a result, this kind of Christological articulation does not explain Christ’s presence in our struggles today. This piece further demonstrates that the context is not above Christ in finding who He is in the midst of such a grave situation; rather, contextual realities provide the Pakistani Punjabi Church an opportunity to demonstrate the works of Christ. Furthermore, this study also argues that the real struggle is not being a minority in this context, but rather, being marginalized (economically, politically, and religiously) is the real challenge. This study further argues that the core issue is the ecclesiastical responsibility to overcome all the issues in this context. The researcher employs quantitative methodology to evaluate the socio-political, socio-economic, and religious perspectives and equips grassroots communities using an evangelical contextual missiological approach. As a result, ‘Apologetic Evangelical Contextual Christology’ is proposed as seeing Christ in all His fullness in the Islamic Context.